Analyzing Exclusion in Global Worker Health Policy - Hilgert, Jeffrey (Relations industrielles / Industrial Relations, 2016)
This article examines the development of the ILO’s Global Strategy on Occupational Safety and Health through the lens of social exclusion. Social exclusion is a transversal concept across the social sciences. The article integrates the study of exclusion as an essential element of institutional analysis in industrial relations. After discussing the treatment of the study of exclusion in labour and employment relations scholarship, it presents an analytic frame using four mechanisms of exclusion taken from sociology: 1- encoding; 2- framing pathways; 3- non-decision making; and 4- mining actualities.Observations are presented from a qualitative study of 125 preparatory and legal texts created through the development of the Global Strategy between 2000 and 2015. The method of analysis is a socio-historic interpretation following the principles of analysis of primary source documents outlined by Marc Trachtenberg in his book The Craft of International History: A Guide to Method. Exclusionary dynamics are observed in three areas: 1- managing the meaning of OSH policy integration; 2- shaping the role of collective labour rights in OSH policy; and 3- sidestepping the development of specific OSH hazard protections. Comparisons are made at key points with recent normative work by UN human rights bodies, including the UN Committee on Economic, Social and Cultural Rights and their General Comment No. 23 on the human right to just and favourable conditions of work. The result is a Global OSH Strategy with promotional strengths, but also neoliberal values interwoven in its policy framework.